1982
DOI: 10.2466/pms.1982.55.3.943
|View full text |Cite
|
Sign up to set email alerts
|

Adults' Performance on a Measure of Visual Closure

Abstract: The Mooney Closure Faces Test has been employed in several studies of right temporal-lobe function. However, the information provided by these studies is somewhat restricted because there has been no systematic attempt to determine what constitutes “normal” performance on this instrument. The present study attempts to rectify partially this situation by testing samples of three distinct populations (college students, vocational-technical students, and relatives of indigent patients) of neurologically intact su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The CHR group was 41% male, and the HC group was 24% male. While this difference was not statistically significant, it is still possible that the difference could have affected group means on the MFT, given prior findings that perception of faces on the MFT may be more pronounced in males [38][39][40] , which is also what we observed. However, evidence that our findings are not due to a gender imbalance between groups is that although female subjects reported fewer faces than males overall, female CHR subjects reported significantly more faces in the upright condition than did HC females, and they reported more faces at a trend level in the inverted condition.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The CHR group was 41% male, and the HC group was 24% male. While this difference was not statistically significant, it is still possible that the difference could have affected group means on the MFT, given prior findings that perception of faces on the MFT may be more pronounced in males [38][39][40] , which is also what we observed. However, evidence that our findings are not due to a gender imbalance between groups is that although female subjects reported fewer faces than males overall, female CHR subjects reported significantly more faces in the upright condition than did HC females, and they reported more faces at a trend level in the inverted condition.…”
Section: Discussionsupporting
confidence: 63%
“…Gender differences and the group x gender interaction were examined using ANOVAs. These were explored because in non-clinical samples, it has been observed that males tend to report perceiving more faces than females on the MFT [38][39][40] . Pearson correlations were calculated both with and without the Hadi correction 56,57 to exclude the influence of outlying values.…”
Section: Discussionmentioning
confidence: 99%
“…The latter finding replicates that of Vigen and colleagues (1982), who also did not observe a significant difference in performance between handedness groups (total N = 100 college students). However, they did observe a significant correlation of performance with age, in that performance deteriorated with age, though for females only (Vigen, Goebel, & Embree, 1982). Although we currently did not observe a correlation of performance with age, for our new Mooney test any analyses of age should be interpreted with caution, since the performance measure depends partially on the participant's dexterity with using a mouse or track pad to click within the correct eye region, a skill on which participants of advanced ages might be impaired.…”
Section: Discussionmentioning
confidence: 96%
“…Foreman (1991), who observed a significantly shorter reaction time for males than for females. Vigen and colleagues reported that sex accounts for 8.5% of the variance in performance on the Mooney Face Test, additionally observing that females' performance declines with increasing age while that of males remains the same (Vigen et al, 1982). These results contrast with findings for other tests of face perception, where females seem to enjoy an advantage on both memory and non-memory based tests, although perhaps for female faces only (Megreya et al, 2011).…”
Section: Introductionmentioning
confidence: 95%